2014
DOI: 10.1530/joe-14-0373
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid treatment and endocrine pancreas function: implications for glucose homeostasis, insulin resistance and diabetes

Abstract: Glucocorticoids (GCs) are broadly prescribed for numerous pathological conditions because of their anti-inflammatory, antiallergic and immunosuppressive effects, among other actions. Nevertheless, GCs can produce undesired diabetogenic side effects through interactions with the regulation of glucose homeostasis. Under conditions of excess and/or long-term treatment, GCs can induce peripheral insulin resistance (IR) by impairing insulin signalling, which results in reduced glucose disposal and augmented endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(140 citation statements)
references
References 115 publications
(158 reference statements)
4
114
0
10
Order By: Relevance
“…Herein, we suggest that hypercorticosteronemia associated with hyperactivity of vagus nerves contributes to functional changes in pancreatic β-cells in MSG-obese rats. In fact, as previously reported, hyperactivity of vagus nerves reduces apoptosis and increases proliferation in pancreatic β-cells (Medina et al 2013), and excessive corticosteroids induce β-cell proliferation leading to insulin oversecretion (Rafacho et al 2014).…”
Section: Figurementioning
confidence: 60%
See 1 more Smart Citation
“…Herein, we suggest that hypercorticosteronemia associated with hyperactivity of vagus nerves contributes to functional changes in pancreatic β-cells in MSG-obese rats. In fact, as previously reported, hyperactivity of vagus nerves reduces apoptosis and increases proliferation in pancreatic β-cells (Medina et al 2013), and excessive corticosteroids induce β-cell proliferation leading to insulin oversecretion (Rafacho et al 2014).…”
Section: Figurementioning
confidence: 60%
“…Surgery causes blunting of ACh release in pancreatic β-cell neuronal ends, which reduces the cholinergic response of glucose-induced insulin secretion (GIIS) (Henquin 2000). Glucocorticoids induce gluconeogenesis, which supports high blood glucose levels in humans and rodents submitted to chronic treatment with glucocorticoids (Rafacho et al 2014). High HPA axis activity induces an enhancement of insulin secretion.…”
Section: Figurementioning
confidence: 99%
“…11 Rafacho et al suggested a strong relationship between peripheral insulin resistance and glucose homeostasis imbalance. 12 The role of serum fructosamine and FBG in elevated glucose homeostasis has been documented in the literature. 13 Therefore, the present study examined the association of serum fructosamine and FBG with major depressive disorder (MDD).…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27] In addition, glucocorticoids induce peripheral insulin resistance. 27) Although the serum concentration of corticosterone increased after the infusion of olanzapine in the present study, no significant difference was noted among the olanzapine dose groups (Fig. 2C).…”
Section: Discussionmentioning
confidence: 99%